The Effect of Using PowerPoint Toward Teaching Writing Analytical Exposition at XI Grade of SMA Negeri 3 Jambi City Academic Year 2018/2019 - Iccha Dhirdhena Prasadat Tungga Dewi; Suyadi Suyadi (JELT: Journal of English Language Teaching, 2019)
This research was aimed to find out whether there was significant effect of using powerpoint toward teaching writing analytical exposition at XI grade SMA Negeri 3 Jambi City. The kind of this research was quantitative research. The data collection involved 72 students, there was consist of 36 students of control class (XI MIPA 5) and 36 students of experimental class (XI MIPA 4) by giving the writing test. The research was Experimental and techniques of analyzing the data of this research apply quantitative data from the scores of pre-test and the scores of post-test. Based on the data, there was significant effect on the studets’ skill in writing analytical exposition text using powerpoint in the result of post-test in experimental class shows from mean of pre-test was 41,20 after doing the treatment with powerpoint there was significant effect of the result of the students’ mean is 71,06. The result of t-test shows that the result of significant value in the experimental class was 0.000<0,05 = there was significant between the result learning with pre-test and post-test data, it was shows that using powerpoint toward teaching writing analytical exposition text real significant to students’ skill ability in writing text.Keywords: PowerPoint,  Analytical Exposition, Writing.